2022
DOI: 10.1021/acsami.2c04599
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic and Single-Crystalline Aluminum–Silicon Heterostructures

Abstract: Overcoming the difficulty in the precise definition of the metal phase of metal−Si heterostructures is among the key prerequisites to enable reproducible next-generation nanoelectronic, optoelectronic, and quantum devices. Here, we report on the formation of monolithic Al−Si heterostructures obtained from both bottom-up and top-down fabricated Si nanostructures and Al contacts. This is enabled by a thermally induced Al−Si exchange reaction, which forms abrupt and void-free metal−semiconductor interfaces in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 59 publications
(80 reference statements)
2
41
0
Order By: Relevance
“…This is well below the Si–Al binary eutectic temperature of 577 °C . It has recently been noted that the exchange rate between Al and Si can be enhanced as the width of the device is decreased, which may explain the reaction we observe here …”
Section: Structural Characterizationsupporting
confidence: 48%
“…This is well below the Si–Al binary eutectic temperature of 577 °C . It has recently been noted that the exchange rate between Al and Si can be enhanced as the width of the device is decreased, which may explain the reaction we observe here …”
Section: Structural Characterizationsupporting
confidence: 48%
“…In contrast, Al-Si junctions show mid-gap Fermi level pinning, resulting in an ambipolar transfer characteristic. [44,62] In this respect, approaches to tune the strength of the Fermi level pinning were already published, as for example, introducing (nitride-)interlayers [14] or layers of carbon nanotubes [63] between the metal and semiconductor, Small 2022, 2204178 utilizing different passivations [64,65] or van der Waals stacking approaches, [66,67] leading to a reduction of the tunneling barrier thickness. Coinciding with a gradual increase of the oncurrent in p-mode (V TG = −5 V), due to a lower band-gap with increasing Ge content and larger carrier concentration, the conductivity of the intrinsic point (point of lowest conductivity) is increasing by orders of magnitude and is shifted to higher gate-voltages for increasing Ge content.…”
Section: Resultsmentioning
confidence: 99%
“…[32] Instead, singleelementary Al contacts to Si/Ge are obtained. [36,44] Moreover, the Al-Si 1−x Ge x material system retains its elementary composition even in the event of applying subsequent annealing steps, thus allowing for the formation of reliable and abrupt metalsemiconductor junctions. In contrast, other metals tend to form various temperature-as well as crystal orientation dependent silicide or germanide alloy phases within the finally obtained structure.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the on‐currents the diameter (here: d NW = 80 nm) needs to be taken into account as well, as it is not possible to fully deplete the semiconductor in comparison to thinner NWs. [ 57 ] Lately, it was shown that the Al‐Si exchange can also be used on SOI‐based nanosheets, [ 38 ] allowing a convenient way to increase on‐current by fabricating parallel arrays of nanosheets. It was also shown that contact printed NWs allow to be integrated in parallel arrays as well.…”
Section: Resultsmentioning
confidence: 99%